Activity inhibition and crystal polymorphism induced by active‐site metal swapping. Issue 8 (1st August 2017) - Yekwa, Elsie; Khourieh, Joelle; Canard, Bruno; Papageorgiou, Nicolas; Ferron, François
Abstract : The effect of ion swapping on the activity of an Arenaviridae exonuclease is reported. Abstract : The Arenaviridae family is one of the two RNA viral families that encode a 3′–5′ exonuclease in their genome. An exonuclease domain is found in the Arenaviridae nucleoprotein and targets dsRNA specifically. This domain is directly involved in suppression of innate immunity in the host cell. Like most phosphate‐processing enzymes, it requires a divalent metal ion such as Mg 2+ (or Mn 2+ ) as a cofactor to catalyse nucleotide‐cleavage and nucleotide‐transfer reactions. On the other hand, calcium (Ca 2+ ) inhibits this enzymatic activity, in spite of the fact that Mg 2+ and Ca 2+ present comparable binding affinities and biological availabilities. Here, the molecular and structural effects of the replacement of magnesium by calcium and its inhibition mechanism for phosphodiester cleavage, an essential reaction in the viral process of innate immunity suppression, are studied. Biochemical data and high‐resolution structures of the Mopeia virus exonuclease domain complexed with each ion are reported for the first time. The consequences of the ion swap for the stability of the protein, the catalytic site and the functional role of a specific metal ion in enabling the catalytic cleavage of a dsRNA substrate are outlined.